Indocyanine green fluorescence angiography-guided simultaneous laparoscopic distal gastrectomy and spleen-preserving distal pancreatectomy for conserving the gastrosplenic ligament: A case report. (March 2022) - Kawaguchi, Shun; Okubo, Satoshi; Haruta, Shusuke; Shindoh, Junichi; Hashimoto, Masaji; Ueno, Masaki
Abstract: Introduction and importance: Indocyanine green (ICG) fluorescence angiography is being increasingly performed intraoperatively to detect restricted blood flow intraoperatively for the prevention of postoperative organ ischemia and anastomotic leakage. This is the first case report of simultaneous laparoscopic distal gastrectomy (LDG) and spleen-preserving distal pancreatectomy (LSPDP) involving ICG angiography use to avoid the remnant stomach ischemia. Case presentation: A 55-year-old man was diagnosed with early cancer of the stomach body and intraductal papillary mucinous neoplasms of the pancreatic tail. We performed simultaneous LDG with D2 dissection and LSPDP to conserve the gastrosplenic ligament and preserve blood supply to the remnant stomach. Intraoperatively, blood flow to the remnant stomach was visualized using ICG fluorescence angiography, after which Roux-en-Y reconstruction was performed. There was no perioperative remnant stomach ischemia. Clinical discussion: Despite the preserved splenic artery and vein, complete splenic infarction occurs after LSPDP possibly due to thrombus formation during surgical procedures. In this patient, we conserved the gastrosplenic ligament for the short gastric artery, which supplied blood to the remnant stomach; however, remnant stomach ischemia may occur. Therefore, we performed ICG fluorescence angiography during this operation to ensure that sufficient blood supply to the remnant stomach was maintained. Conclusion: Our experience demonstrates that ICG angiography may be useful for the prevention of remnant stomach ischemia. Highlights: Remnant stomach ischemia could occur in simultaneous gastrectomy and pancreatectomy. Our patient had early gastric cancer and intraductal papillary mucinous neoplasm. He had laparoscopic distal gastrectomy and spleen-preserving distal pancreatectomy. Remnant stomach perfusion was visualized using indocyanine green angiography. Postoperative remnant stomach ischemia did not occur.